Biosafety and efficacy evaluation of a biodegradable Zn-Cu-Mn stent: A long-term study in porcine coronary artery - Yi Qian; Yan Chen; Jimiao Jiang; Jia Pei; Junfei Li; Jialin Niu; Jinzhou Zhu; Guangyin Yuan (Bioactive Materials)
In this study, biodegradable Zn-Cu-Mn alloy stents were implanted into porcine coronary artery for 18 months, and the in vivo biosafety and efficacy as well as the degradation behavior were systematically studied. Results showed a rapid endothelialization of the target vessel was achieved at 1 month post-implantation. Although the lumen diameter loss and local inflammation were observed at the early stage, the stented blood vessel could gradually recover with time. The lumen diameter was already close to normal range at 12 months, indicating good bioefficacy of the stent. No adverse effect on blood indexes or local accumulation of Zn, Cu or Mn elements were found after implantation, neither the malapposition and thrombosis were observed, which exhibited good biosafety of the stents. The stent could maintain the basic structure and mechanical integrity at 6 months, and remained only approximately 26 % of the stent volume at 18 months, suggesting a desirable degradation rate. In general, the Zn-Cu-Mn alloy stent showed great advantages and prospects in clinical application.